A viable approach to repair neutron shielding B4C/6061 Al composite sheets through cold spray and hot rolling co-treatment. (20th April 2022) - Qiu, Xiang; Qi, Lu; Tang, Jun-rong; Tariq, Naeem ul Haq; Wang, Ji-qiang; Xiong, Tian-ying
Highlights: A repairing approach for restoring neutron shielding composite plates was presented. Defected plate was subjected to cold sraying followed by hot rolling treatments. Hot rolling resulted in improved microstructure of the as-sprayed deposit. 3-point bend test confirmed good strength of the repaired material. Abstract: Cold spray (CS) is considered as a new type of repairing technique for restoration or remanufacturing of a wide range of unserviceable engineering components due to its unique 'cold' characteristic. In this work, a viable repairing approach i.e. "cold spraying followed by hot rolling post-treatment" was successfully applied to restore defective neutron shielding B4 C/6061 Al composite plates. Scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD) results revealed that the coating-substrate interface is in a good bonding state without micro-cracks. Hot rolling post-treatment resulted in improved microstructure of the as-sprayed deposit with more uniform distribution of B4 C particles in the matrix. Moreover, well bonded splat boundaries and strain free Al grains were evolved in the matrix due to enhanced splat deformation and continuous dynamic recrystallization (CDRX). Three-point bending test results revealed that the strength of the repaired material is at par with the in-service plates. The findings of this work could be considered as a great stride to further extend possible applications of CS for repairing engineering structural components.